Библейские аллюзии в исторических хрониках Вильяма Шекспира - Никольский, Евгений Владимрович; Nikolskiy, Evgeniy; Солдаткина, Янина Викторовна; Soldatkina, Yanina (Східноєвропейський національний університет імені Лесі Українки, 2016)
В статье рассматриваются библейские мотивы и аллюзии, скрытые в исторических хрониках Вильяма Шекспира. Проанализированы основные библейские прообразы шекспировских героев, раскрыта нравственная проблематика, базирующаяся на Священном Писании. Отмечается, что драматург использует точные и варьированные цитаты, применяет библейские аллюзии, реминисценции, сюжетные интерпретации, выполня¬ющие также функции характеристики образов и выражения авторского мнения.The article discusses the hidden biblical motifs and allusions hidden in the historical Chronicles of Shakespeare. Analysis of the principal biblical prototypes of Shakespeare's characters, revealed moral problems, based on Scripture. Іt is noted that the playwright uses accurate and varied quotations, uses of biblical allusions, reminiscences, narrative interpretation, which performs functions of the characteristics of the images and expressions of the author's opinions.
Biblical Allusions in the Histories of William Shakespeare
Keywords: библейский интертекст; аллюзия; реминисценция; выражение авторского сознания, сюжетные интерпретации; царственная святость; праведность; провиденциализм; образ праведного монарха; biblical intertext; allusion; reminiscence; expression of author's consciousness; plot twist; Regal Holiness; righteousness; providentialism; the image of a righteous monarch